รูปแบบขององค์กรร่างรัฐธรรมนูญตามแนวคิดรัฐธรรมนูญนิยมที่เหมาะสมสำหรับประเทศไทย - ปรางทิพย์ พรวัฒนะกิจ (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
Since Thailand had changed the rule of the state from Absolute Monarchy to Democracy with the King as the head of the state in B.E. 2475, Thailand has 18 constitutions. However, it appears that the 18 constitutions were not all drafted in accordance with the concept of constitutionalism which is the foundation of the constitution in the democratic countries. Nonetheless, some includes the concept into the constitution, entirely or partly. Hence, most of the constitutions were not drafted according to the three objectives of the constitution in the democratic countries. Firstly, constitutions do not guarantee important rights and liberty of the people. Secondly, the constitutions missed the concept of separating and balancing of powers. Lastly, the constitutions do not build stability and efficiency to the governments. Considering the constitution drafting process, the form of the drafting entity is one of the factors that affects constitutionalism-complied constitution. Accordingly, the objective of this study is to determine which form of the constitution drafting entity is the most appropriate for Thailand.The study found that Federal Republic of Germany, Republic of Korea, France and Japan succeeded in drafting constitutionalism-complied constitution. Moreover, such constitutions could help the countries in their political reform. The drafting process of the four countries is having the experts in specific fields to analyze problems and weaknesses of their present constitutions and being able to prepare the first draft of the constitutions before sending it to be reviewed by the constituent assembly. However, Thailand has never had such experts in specific fields to analyze problems and weaknesses of the present constitution or prepare the first draft. Therefore, going forward if Thailand were to draft the new constitution, the experts in specific fields can be used as an alternative. With the expertise of the experts, the new constitutionalism-complied constitution might be drafted.